2002
DOI: 10.1002/mc.10091
|View full text |Cite
|
Sign up to set email alerts
|

Gradual deregulation and loss of PCPH expression in the progression of human laryngeal neoplasia

Abstract: PCPH is a gene involved in the regulation of eukaryotic cell proliferation and stress response. Recently, analyses of human and animal solid tumors and cell lines suggested that PCPH protein deregulation may participate in neoplastic progression. To test this possibility, we first examined PCPH expression in several laryngeal carcinoma cell lines by Western analysis. The results showed the presence of altered PCPH polypeptides in these cells, accompanied by the loss of the PCPH form present in normal laryngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
(66 reference statements)
2
17
0
Order By: Relevance
“…2-4), a pattern similar to that described previously for PCPH in samples of human laryngeal dysplasia (7), in which PCPH is expressed at lower levels in severe than in mild dysplastic cases and at much lower levels than in the normal laryngeal mucosa (7). The preferential expression of PCPH in well-differentiated slowly proliferating cells rather than in less-differentiated more actively proliferating cells is consistent with the detection in mature teratoma samples of higher levels of PCPH expression in cells of the basal layer than in suprabasal cells (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…2-4), a pattern similar to that described previously for PCPH in samples of human laryngeal dysplasia (7), in which PCPH is expressed at lower levels in severe than in mild dysplastic cases and at much lower levels than in the normal laryngeal mucosa (7). The preferential expression of PCPH in well-differentiated slowly proliferating cells rather than in less-differentiated more actively proliferating cells is consistent with the detection in mature teratoma samples of higher levels of PCPH expression in cells of the basal layer than in suprabasal cells (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…No background staining to PCPH was observed in any of these controls (data not shown). Samples from normal laryngeal mucosa were used as positive controls and yielded results consistent with previously published data (7). Analysis of the seminoma samples showed that PCPH was expressed in all cases.…”
Section: Immunohistochemical Detection Of Pcph In Samples Of Seminomasupporting
confidence: 76%
See 3 more Smart Citations